ARE CHILDREN'S ALIMONY RIGHTS GUARANTEED: AN ANALYSIS OF JUDICIAL PRACTICE? - Джалилов Азамат Амриллоевич (Ecominds Press, 2026)
The article examines the issues of guaranteed implementation of children's alimony rights based on the analysis of judicial practice. The legal essence of the institution of alimony, the fundamentals of the emergence of alimony obligations and the theoretical aspects of their implementation are covered by the analysis of scientific literature. On the basis of the decisions of the appeal of the Surkhandarya Regional Court and the statistical data of the Supreme Court of the Republic of Uzbekistan for 2020-2024, the consideration of court cases on the collection of alimony payments was evaluated. The article reveals shortcomings in the activities of the compulsory enforcement agencies, problems of late payment of alimony payments and difficulties in ensuring the interests of the child. The author has developed practical proposals for making changes in the legislation to ensure the effective implementation of alimony obligations.
Keywords: Alimony rights, child interests, judicial practice, alimony obligations, compulsory enforcement, court order, alimony collection, enforcement documents, improvement of legislation, Family Code.